Effects of annealing in Te2 atmosphere on photoelectric properties and carrier transport properties of CdZnTe films. (January 2023) - Wan, Xin; Li, Yang; Tan, Tingting; Liu, Yajie; Wei, Heming; Cao, Kun; Zha, Gangqiang
Abstract: CdZnTe (CZT) epitaxial films were deposited on GaAs substrates by closed spaced sublimation. In order to reduce the adverse effects of point defects and dislocations in the film on its properties, CZT films were annealed at 400 °C in Te2 atmosphere at different times. The I–V test and energy spectrum show that the resistivity of CZT films increased from 10 9  Ω cm to 10 10  Ω cm, and the electron mobility lifetime product ( μτ )e increased from 10 −5  cm 2  V −1 to 10 −4  cm 2  V −1 . According to the etch pit density and photoluminescence tests, the results show that annealing reduced the dislocation density from 3.28 × 10 5  cm −2 to 2.52 × 10 5  cm −2 in the CdZnTe films. In this study, the annealing process which can stably improve the properties of CdZnTe films is obtained, that is, annealing at 400 °C in Te2 atmosphere for 2–4 h. Highlights: The resistivity of CdZnTe films improved from 10 9  Ω cm to 10 10  Ω cm. The electron mobility lifetime product (μτ)e of CZT films increased from 10 −5  cm 2  V −1 to 10 −4  cm 2  V −1 . The dislocation density of CZT films reduced from 3.28 × 10 5 cm −2 to 2.52 × 10 5 cm −2 .